2021
DOI: 10.1088/1755-1315/640/2/022085
|View full text |Cite
|
Sign up to set email alerts
|

Composition of biologically active substances of Vaccinium berries growing in the northwestern region of Russia

Abstract: Using gas chromatography with preliminary derivatization of samples, the composition of the biologically active substances of wild-growing cranberries (Vaccinium oxycoccos L.) and lingonberries (Vaccinium vitis idaea L.) was studied. Biologically active substances contain phenolic compounds, tocopherols and phytosterols. Flavonoids prevail in the composition of phenolic compounds, the amount of which increases in berry press residues. Cranberries and lingonberries differ in the quantitative and qualitative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
0
1
Order By: Relevance
“…In a study by Klavins et al, the β-Sitosterol content of 3150 µg/g found in the extract of the waxy layer of large cranberry fruit was higher than the amount of β-Sitosterol found in our study [ 22 ]. Meanwhile, in a study by Nilova et al, the level of β-Sitosterol (4 µg/g) found in berry press residues of cranberries was significantly lower than that detected in our study [ 50 ].…”
Section: Resultscontrasting
confidence: 94%
“…In a study by Klavins et al, the β-Sitosterol content of 3150 µg/g found in the extract of the waxy layer of large cranberry fruit was higher than the amount of β-Sitosterol found in our study [ 22 ]. Meanwhile, in a study by Nilova et al, the level of β-Sitosterol (4 µg/g) found in berry press residues of cranberries was significantly lower than that detected in our study [ 50 ].…”
Section: Resultscontrasting
confidence: 94%
“…The TFC concentration range of the fruits at different altitudes and ripeness stages ranged from 12.44 to 37.71 mg Cateq/g FW ( Table 4 ). Previous studies on V. floribundum Kunth [ 43 , 44 ], V. corymbosum L. [ 60 ], and Vaccinium vitis idaea L. [ 61 ] corroborate our results. According to the results obtained, TFC was also affected by the different altitudes of the production sites and the ripeness stage.…”
Section: Discussionsupporting
confidence: 91%